(untitled) (Bangladesh Journal of Agricultural Research, 2015)
Thirty genotypes of wheat were grown in an Alpha Lattice Design with three replications for evaluation and divergence analysis. Seeds were sown on 24 November 2011 at Regional Wheat Research Centre, Bangladesh Agricultural Research Institute, Shyampur, Rajshahi. Significant variation was observed among the genotypes and these are grouped into six clusters. Clusters III and VI were comprised of maximum number of genotypes (6) followed by clusters I, IV, and V with 5 genotypes and the minimum genotypes (3) were in cluster II. The maximum inter-cluster distance was recorded between the Cluster VI and Cluster II followed by cluster III and Cluster II, which indicates that genotypes belonging to these distant clusters could be used in hybridization programme for getting a wide spectrum of variation among the segregates. The minimum intercluster distance was found between the Cluster IV and Cluster I followed by that of Cluster V and Cluster IV. The maximum intra-cluster distance was recorded in Cluster II, consisted of three genotypes of diverse origin followed by Cluster V consisting of five genotypes which indicated that the genotypes of these clusters might have considerable diversity among themselves. While the minimum distance was computed in Cluster I composed of five genotypes which indicated that these genotypes were genetically very close to each other. Considering the eigenvalues of all principal component analysis the PC1, PC2, PC3, PC4, and PC5 with values contributed 30.78%, 20.11%, 17.75%, 10.93%, and 7.63%, respectively, of the total variation. The results revealed from the present study that the first principal component had high positive component loading from grains/spike and high negative loading from grain yield. Considering the clusters mean value, the genotype of Cluster II and VI are most divergent and maximum heterosis and wide variability in genetic architecture may be expected from the crosses between the genotypes belonged to these clusters. More specifically the cluster II could be selected for dwarf in nature, early heading and maturity and bold grain size. The genotypes from the cluster IV could be selected for maximum spikes/m2 and maximum grain yield. The positive value of both vectors for days to heading and spikes/m2 indicated that these traits had the highest contribution towards divergence among the 30 drought tolerant wheat genotypes. DOI: http://dx.doi.org/10.3329/bjar.v39i3.21982 Bangladesh J. Agril. Res. 39(3): 385-396, September 2014